2003
DOI: 10.1093/cercor/13.10.1023
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Perception of Facial Affect and Identity in the Human Brain

Abstract: Functional magnetic resonance imaging (fMRI) was used to compare brain activation to static facial displays versus dynamic changes in facial identity or emotional expression. Static images depicted prototypical fearful, angry and neutral expressions. Identity morphs depicted identity changes from one person to another, always with neutral expressions. Emotion morphs depicted expression changes from neutral to fear or anger, creating the illusion that the actor was 'getting scared' or 'getting angry' in real-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
231
3
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 297 publications
(266 citation statements)
references
References 94 publications
28
231
3
4
Order By: Relevance
“…Passive viewing of still images of bodily expressions activates areas in the occipitoparietal pathway reaching the SMA, cingulate gyrus, and middle frontal gyrus, which has been detected during the observation of actions with the intent to imitate later and voluntary action (42,44), and suggests that passive viewing can initiate motor preparation. Activity in caudate nucleus was also observed for motion stimuli (46). Interestingly, the present activations may follow from a process whereby the brain fills in the missing dynamic information (47).…”
Section: Discussionsupporting
confidence: 59%
“…Passive viewing of still images of bodily expressions activates areas in the occipitoparietal pathway reaching the SMA, cingulate gyrus, and middle frontal gyrus, which has been detected during the observation of actions with the intent to imitate later and voluntary action (42,44), and suggests that passive viewing can initiate motor preparation. Activity in caudate nucleus was also observed for motion stimuli (46). Interestingly, the present activations may follow from a process whereby the brain fills in the missing dynamic information (47).…”
Section: Discussionsupporting
confidence: 59%
“…Each face was discrimination in a statistical model, so that identity discrimination was still possible when analysis was restricted to components selective for expression discrimination and vice versa. Neuroimaging studies have also shown a large overlap in activation patterns and associated processes drawn upon during identity and facial expression recognition tasks (e.g., LaBar, Crupain, Voyvodic, & McCarthy, 2003). Facial speech processing, another changeable aspect of the face, has similarly been shown to interact with identity processing (Walker, Bruce, & O'Malley, 1995).…”
Section: Experiments 1 Methodsmentioning
confidence: 99%
“…The superior temporal sulcus is increasingly being regarded as a higher-order processing region for the integration of multisensory stimuli and motion perception (Grossman & Blake, 2002;Jellema, Maassen, & Perrett, 2004;LaBar, Crupain, Voyvodic, & McCarthy, 2003; J. P. Morris, Pelphrey, & McCarthy, 2005;Pasternak & Merigan, 1994;Pelphrey, Mitchell, et al, 2003). To separate unique brain activation to motion cues from other contextual factors, researchers have frequently used highly degraded visual stimuli such as point-light displays (Heberlein, Adolphs, Tranel, & Damasio, 2004).…”
Section: Superior Temporal Sulcusmentioning
confidence: 99%